Strategic trading and trade reporting by corporate insiders - André Betzer; Jasmin Gider; Daniel Metzger; Erik Theissen (University of Wuppertal, Schumpeter School of Business and Economics, 2011)
Regulations in the pre-Sarbanes-Oxley era allowed corporate insiders considerable flexibility in strategically timing their trades and SEC filings, e.g., by executing several trades and reporting them jointly after the last trade. We document that even these lax reporting requirements were frequently violated and that strategic timing of trades and reports was common. Event study abnormal returns are larger after reports of strategic trades than after reports of otherwise similar nonstrategic trades. Our results imply that delayed reporting impedes the adjustment of prices to the information revealed by insider trades. They lend strong support to the more stringent reporting requirements established by the Sarbanes-Oxley Act.
urn:nbn:de:hbz:468-20111111-103006-5
Keywords: G14; G30; G32; 330; Insider trading; directors' dealings; corporate governance; market efficiency; Insiderhandel; Publizitätspflicht; Insiderrecht; Börsenkurs; Markteffizienz; Internes Kontrollsystem; USA